Pengaruh Kompetensi Dan Beban Kerja Terhadap Perilaku Perawat Dalam Menerapkanasuhan Keperawatan Profesional Di Instalasi Rawat Inap RSUD Praya (Jurnal Kesehatan Qamarul Huda, 2019)
Nursing services are an integral part of health services which have a very strategic position in an effort to improve the quality of services in hospitals. With this condition a nurse is required to have the ability and professionalism in implementing professional nursing care in a hospital service. The purpose of this study was to determine the effect of competency factors, and workload on nurses' behavior in implementing professional nursing care in the Praya Hospital inpatient installation. The research design used was quantitative analytic with cross sectional approach. The sampling technique uses cluster random sampling with a sample of 114 respondents. Data were collected using a questionnaire and observation sheet, then analyzed using the ordinal regression test. The results of the statistical test by stimulatory results obtained p value of 0,000